Medication delivery errors in outpatients with percutaneous endoscopic gastrostomy: effect on tube feeding replacement - David García González; Ana Martín-Suárez; Juan José Salvador Sánchez; Jesús Ángel Sánchez Serrano; M. Victoria Calvo (Scientific Reports, 2023)
Abstract Patients with enteral access usually receive oral drugs via feeding tubes and correct drug administration remains a challenge. The aim of this study was to identify common medication delivery errors (MDEs) in outpatients with percutaneous endoscopic gastrostomy (PEG) and evaluate their association with the need for tube replacement due to deterioration or clogging. A 2-year retrospective study that comprised adult outpatients with a placed/replaced PEG tube and whose electronic medical record included home medication was carried out. Treatment with medication that should not be crushed and administered through an enteral feeding tube was considered an MDE. We included 269 patients and 213 MDEs (20% of oral prescriptions) were detected in 159. Ninety-two percent of the medications associated with MDEs could be substituted by appropriate formulations. Tube replacement due to obstruction was needed in 85 patients. MDEs were associated with increased risk for tube replacement (OR 2.17; 95% CI 1.10–4.27). Omeprazole enteric-coated capsules were associated with the greatest risk (OR 2.24; 95% CI 1.01–4.93). PEG outpatients are highly exposed to MDEs, leading to a significant increase in the odds of tube replacement, mainly when treated with omeprazole. The use of appropriate alternative therapies would prevent unnecessary adverse events.